J-Synch protocol associated with estrus detection in beef heifers and non-lactating cows - Mion, Bruna; Bonotto, Ramiro Martins; Farias, Caroline Oliveira; Rosa, Fernanda Souza; Pradiee, Jorgea; Rovani, Monique Tomazele; Pegoraro, Lígia Margareth Cantarelli; Bonotto, Ana Lúcia Martins; Pfeifer, Luiz Francisco Machado; Schneider, Augusto (Medicina Veterinária, 2020)
The aim of this study was to compare the J-Synch and conventional protocols associated with estrus detection in beef heifers and to compare pregnancy rate between non-lactating cows displaying estrus or not during the J-Synch protocol. In Experiment 1, heifers were subjected to timed artificial insemination (AI) in a conventional protocol with ECP (n=147) or J-Synch protocol plus eCG (n=149). The AI occurred 12 hours after estrus expression; or 48 (Conventional protocol) and 72 hours (J-Synch protocol) after device removal for animals not displaying estrus. The J-Synch group received 10 µg of GnRH at AI. In Experiment 2, the JSynch was performed (n=116 cows), but without eCG injection, and estrus was monitored. Pregnancy rate was not different between protocols in Experiment 1 (Conventional: 50.68%; J-Synch: 60.4%). Heifers that displayed estrus had higher pregnancy rate only in the conventional protocol. In Experiment 2, pregnancy rate was not different between cows that displayed estrus or not. Therefore, performing AI earlier according to estrus expression increases pregnancy rate in conventional protocol, however it does not increase pregnancy rate in the J-Synch protocol.